AUTHOR INDEX/INDEX DES AUTEURS - Angus, Don; Auster, Ethel; Bodorik, P.; Brookes, Bertram C.; Crawford, R. G.; Deschatelets, Gilles; De Solla Price, Derek; Dykstra, Mary; Gallina, Paul Leonard; Grundke, G. W.; Heaps, H. S.; Kincaid, Keith; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF